Protesting for autocracy: economic vulnerability and anti-democratic protest attendance in Tunisia. Issue 2 (17th February 2023) - Ash, Konstantin
ABSTRACT: Economic vulnerability has been linked to pro-democracy protests in autocracies. This study suggests that the economically vulnerable are also more likely to participate in protests in support of autocracy in democracies. When democratically-elected governments are perceived as incapable of resolving economic problems, but are not democratically removable, the economically vulnerable should gather and call for an authoritarian takeover. The theory is tested through a representative survey of 1, 000 Tunisian respondents. Results show underemployed Tunisians are generally more likely to say they would attend protests demanding military intervention and significantly more than protests demanding local reform. The findings suggest that just as economically vulnerable individuals can destabilize autocracies through protest, they can also destabilize unconsolidated democracies through public agitation for authoritarianism.